Generalized Schuster law and King’s formula - Živkov V.; Ninković S. (Serbian Astronomical Journal, 1998)
By varying a particular form of the generalized Schuster density law (the exponent in the denominator equal to 3/2) the authors look for a suitable substitution for King’s density formula usually applied to star clusters and dwarf galaxies. The authors find expressions yielding almost identical density values as King’s formula, but from the mathematical point of view significantly more simple for use.